Isolation and Antibacterial Activity of Sembung (Blumea balsamifera) Leaf Essential Oil L., DC - Afriani, Tika; Rahmi, Azimatur; Sari, Mia Darmita (Biology, Medicine, & Natural Product Chemistry, 2024)
Sembung leaf essential oil is a complex mixture in the form of oily yellow liquid with a unique aroma. It contains various volatile components that have antibacterial, antifungal, antioxidant and cytotoxic activities. This study aims to determine the antibacterial activity of essential oil Blumea balsamifera L., DC against Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus. Isolation of essential oil using steam distillation method with 0.21% rendement. Inhibition activity was performed by test tube method with variation concentrations of essential oil were 10%, 20%, 40%, 80%, and 100% for each bacteria. Results of this study showed that the highest antibacterial activity on Escherichia coli at 80% concentration with an inhibition zone diameter of 27.53 mm, 100% concentration for Pseudomonas aeruginosa with an inhibition zone diameter 25.72 mm and 100% concentration for Staphylococcus aureus with inhibition zone diameter 27.31 mm. Essential oil from (Blumea balsamifera) L., DC leaves have a strong activity inhibition category against Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus.